2021
DOI: 10.1017/ipm.2021.65
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in older adults with intellectual disability: a scoping review

Abstract: Introduction: Ireland has an ageing population of persons with intellectual disability (ID), autism spectrum disorder (ASD) and both (ID/ASD). Despite this, little is known about the prevalence of ASD and its effect on functional outcomes, psychiatric comorbidity or diagnostic issues in an older population with ID. This article reviews the literature on older adults with ID/ASD and identifies opportunities for future research in this population. Method: The authors searched the Medline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Studies reported a variety of desired supports including social skills, education/employment, self-care, and mental health, which are often unmet (Baldwin & Costley, 2016 ; Crane et al, 2018 ; Griffith et al, 2012 ; Jones et al, 2014 ). Studies of autistic adults with intellectual disability found them to have poorer adaptive functioning skills, more co-occurring psychiatric conditions, and more behaviours of concern compared to their non-autistic peers, suggesting greater support needs (Maguire et al, 2022 ; McCarthy et al, 2010 ; Totsika et al, 2010 ). Most research into supports and interventions for autistic adults with and without intellectual disability was focused on social skills (Lorenc et al, 2017 ; Walton & Ingersoll, 2013 ).…”
Section: Support For Autistic Adultsmentioning
confidence: 99%
“…Studies reported a variety of desired supports including social skills, education/employment, self-care, and mental health, which are often unmet (Baldwin & Costley, 2016 ; Crane et al, 2018 ; Griffith et al, 2012 ; Jones et al, 2014 ). Studies of autistic adults with intellectual disability found them to have poorer adaptive functioning skills, more co-occurring psychiatric conditions, and more behaviours of concern compared to their non-autistic peers, suggesting greater support needs (Maguire et al, 2022 ; McCarthy et al, 2010 ; Totsika et al, 2010 ). Most research into supports and interventions for autistic adults with and without intellectual disability was focused on social skills (Lorenc et al, 2017 ; Walton & Ingersoll, 2013 ).…”
Section: Support For Autistic Adultsmentioning
confidence: 99%